The Role of Social Performance, Governance System and Spiritual Compliance in Improving the Financial Performance of Sharia Commercial Banks in Indonesia - Jhody Wiraputra; Ridwansyah; Yulia Andriani; Palupi Pratiwi (Al-Muamalah: Jurnal Ekonomi Islam, Filantropi dan Perbankan Syariah, 2025)
This study aims to examine the role of Islamic Corporate Social Responsibility (ICSR), Good Corporate Governance (GCG), and Zakat Performance Ratio (ZPR) in improving the financial performance of Sharia commercial banks (BUS) in Indonesia during the period 2019-2023. Financial performance in this study proxied using Return on Asset (ROA). Using quantitative methods with panel data regression approach and the best Fixed Effect Model, the research sample consisted of 6 buses that meet the criteria of purposive sampling. The results showed that partially, ICSR and ZPR variables did not positively affect the financial performance of the BUS. These findings imply that increased social activity and zakat disbursements have not been significantly translated by the market as improved short-term financial performance. However, GCG variables were found to have a positive and significant effect on financial performance, emphasizing that good corporate governance practices are the main drivers of BUS financial performance. Overall, these results suggest that strengthening GCG is a key focus that management should emphasize to improve the financial performance of buses.